2018
DOI: 10.30739/darussalam.v10i1.276
|View full text |Cite
|
Sign up to set email alerts
|

Toleransi Beragama Masyarakat Bali, Papua, Maluku

Abstract: The focus of this research is the tolerance of the people of Bali, Maluku, and Papua. This quantitative research uses a survey method by taking 282 respondents who are at least 20 years old. As a result, 61.3% of respondents were the same with people of different religions and religions. 85.3% remained friends despite their religious differences. 60.6% of respondents still feel happy and comfortable with people who have different beliefs. And 66.3% of respondents often gave appreciation to friends and neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
1
1
0
4
Order By: Relevance
“…The contributions made by migrants at the research location show that harmony in the Parhayangan sector is already running well and needs to be maintained in the future. Religious tolerance is very high, in line with research by Faridah [11], Hermawati et al [12], Basyir [13], Amalia and Nanuru [14], Desky [15], who found that between followers of different religions, there was never any conflict, instead they collaborated between religious groups. Religion and belief are individual matters where there is an awareness of mutual respect and an agreement not to disturb other people's beliefs.…”
Section: Forms Of Migrant Participation In Carrying Out Awig-awig Tra...supporting
confidence: 75%
“…The contributions made by migrants at the research location show that harmony in the Parhayangan sector is already running well and needs to be maintained in the future. Religious tolerance is very high, in line with research by Faridah [11], Hermawati et al [12], Basyir [13], Amalia and Nanuru [14], Desky [15], who found that between followers of different religions, there was never any conflict, instead they collaborated between religious groups. Religion and belief are individual matters where there is an awareness of mutual respect and an agreement not to disturb other people's beliefs.…”
Section: Forms Of Migrant Participation In Carrying Out Awig-awig Tra...supporting
confidence: 75%
“…The subjects of this study are the Rinduan Zain & Zahrotun Salimah Muslim communities of Bali, Papua, and Maluku, who are minorities in their area. The tolerance of the Muslim community in these three areas is in the high category, as evidenced by the people who can live side by side with followers of other religions and do not prevent followers of other faiths from worshipping (Amalia & Nanuru, 2018). So, religious differences do not affect a person's tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Hal tersebut selaras dengan salah satu penyebab kasus intoleran menurut Staf Khusus Ketua Dewan Pengarah Badan Pembinaan Ideologi Pancasila (BPIP) Romo Antonius Benny Susetyo yaitu pendirian rumah ibadah yang sangat sulit dan hak-hak minoritas (Pusdatin 2020). Integritas antara sosial dan agama harus kuat agar tidak saling tumpang tindih (Amalia and Nanuru 2018). Sehingga dengan adanya toleransi dapat mewujudkan negara yang adil, sejahtera dan demokratis (Amalia and Nanuru 2018).…”
Section: Pendahuluanunclassified